EFEKTIVITAS PENGGUNAAN APLIKASI KAHOOT SEBAGAI PENILAIAN PEMBELAJARAN DIGITAL TERHADAP MOTIVASI BELAJAR SISWA - Fitriyeni; Siti Quratul Ain; Indah Kurniati; Chintiya Putri Ardya Pramesti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Digital learning assessment is one of the important innovations in modern education that can improve the quality of the teaching and learning process through the use of technology. One of the applications currently widely used in learning assessment is Kahoot. Kahoot is a game-based learning platform that allows teachers to conduct assessments in an interactive, fun, and easily accessible way for students. This study aims to determine the effectiveness of using the Kahoot application as digital learning assessment on the learning motivation of primary school students. The research method used is quantitative. The research sample consists of 30 fifth-grade students from SDN 120 Pekanbaru. The research instruments include a student learning motivation questionnaire. The questionnaire was administered after the students used the Kahoot application in learning assessment. The questionnaire was administered with the aim of observing the students' responses to the use of the Kahoot application in learning assessment. The results of the study show that 14.11% always, 29.63% often, 21.16% sometimes, 25.40% rarely, and 9.70% never.